1996
DOI: 10.1046/j.1365-2567.1996.458547.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of polymorphic residues of human leucocyte antigen‐DR molecules on the binding of human immunodeficiency virus peptides

Abstract: SUMMARYA study was made of the binding properties of 96 human immunodeficiency virus peptides to human leucocyte antigen (HLA)-DR1 and HLA-DR103 molecules, which differ by three amino acids at positions 67, 70 and 71 in the b chains. The affinity of the peptides was characterized by their inhibitory concentrations in competitive binding assays which displace half of the labelled influenza haemagglutinin peptide ). Among the high-affinity peptides (IC 50 4 1 m M), seven bound to DR1, three to DR103 and five eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Similarly, Fu et al (25) demonstrated that an A 74 →E 74 substitution inhibited T cell responses to hemagglutinin peptide 307–319 without inhibiting peptide binding. In contrast, Jurcevic et al (26) demonstrated that positions 67 and 71 contributed equally and synergistically to human immunodeficiency virus peptide binding to DRB1*01:03. More recently, Menconi et al (27) reported that DRB1 residues 67 and 74 are strongly associated with the development of autoimmune polyglandular syndrome.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Fu et al (25) demonstrated that an A 74 →E 74 substitution inhibited T cell responses to hemagglutinin peptide 307–319 without inhibiting peptide binding. In contrast, Jurcevic et al (26) demonstrated that positions 67 and 71 contributed equally and synergistically to human immunodeficiency virus peptide binding to DRB1*01:03. More recently, Menconi et al (27) reported that DRB1 residues 67 and 74 are strongly associated with the development of autoimmune polyglandular syndrome.…”
Section: Discussionmentioning
confidence: 93%
“…Purification of HLA-DR molecules HLA-DR molecules were purified essentially as described before [14,15]. Briefly, Epstein-Barr virus (EBV)-transformed HLA-DR homozygous lymphoblastoid B cell lines (LBL), HOM-2, MGAR, VAVY, BOLETH, SWEIG, AMALA, MOU, MADURA and DKB, were lysed at 10 8 cells/ml in PBS containing 1% NP-40, 0 .…”
Section: Synthetic Peptidesmentioning
confidence: 99%
“…The HIV peptides show high affinity to the HLA-DR moieties. A study has also demonstrated the high affinity of certain HIV-derived peptides to the HLA-DR on the cell surface [48]. Studies indicate that the HLA-DR is incorporated into the viral envelope at the budding stage of the HIV cycle and facilitates further infection of the other uninfected cells using the CD4 receptor as the receptor.…”
Section: Hla-drmentioning
confidence: 99%